Isolation of a High Potential Thermotolerant Strain of Zymomonas mobilis for Ethanol Production at High Temperature Using Ethyl Methane Sulfonate Mutagenesis - Jatupat Samappito (Science Faculty of Chiang Mai University, 2019)
The wild-type strain Zymomonas mobilis TISTR548 has a critical temperature for its growth and ethanol production at 38 C. To obtain a high potential thermotolerant strain of this ethanologenic bacterium, this wild-type strain was subjected to chemical mutagenesis using ethyl methane sulfonate (EMS). After EMS treatment, the mutagenized cells were screened at temperatures ranging from 38 to 40 C. The results showed that only six mutant strains, designated ZM EMS-52, ZM EMS-121, ZM EMS-143, ZM EMS-229, ZM EMS-263 and ZM EMS-297, could grow and produce a relatively high level of ethanol at 40 C. Among these mutants, ZM EMS-229 displayed higher growth and ethanol production capacity than did the wild-type and other mutants at 37 and 40 C. This mutant strain also showed greater resistance to high concentrations of ethanol, acetic acid and H2O2 at high temperature than did the wild-type. These findings suggested that the ZM EMS-229 was a good candidate for high-temperature ethanol fermentation.